PROFESSIONAL COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN THE DIGITAL ERA - Risma, Risma; AZ, Sutiono; Rodhiyana, Mu'allimah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
The problems faced by PAI teachers in the digital era are very diverse, ranging from the inability to use technology to the difficulty of instilling Islamic values through digital media. PAI teachers must improve their technological skills and develop learning methods that suit the needs of students in the digital era. In addition, the government, schools, and educational institutions must support overcoming this problem and creating an inclusive and relevant learning environment amid rapid technological development. The type of research used is library research or literature study. Researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. The result of this research is that PAI teachers in the digital era face challenges regarding access to technology, digital literacy, and adaptation of learning methods. However, this era also offers many opportunities to enrich learning through technological innovation, wider access to learning resources, and continuous professional development. By mastering technology, PAI teachers can strengthen religious learning that is interactive, and relevant and maintains spiritual values in the digital world. The competence of PAI teachers in the digital era includes not only mastery of Technology, but also the ability to integrate religious values with the appropriate use of technology in education, as well as continuing to innovate in teaching methods.